Assisted Reproductive Technology and Origins of Disease: The Clinical Realities and Implications - Morin, Scott J.; Seli, Emre (Seminars in Reproductive Medicine, 2018)
The majority of offspring born following assisted reproductive technology (ART) achieve equivalent development milestones and demonstrate comparable health as spontaneously conceived children. Yet, multiple studies have suggested offspring conceived with ART have slightly increased risk of metabolic derangements, cardiovascular disease, and malignancy. However, the associations observed in these studies often inadequately control for a variety of confounding variables, such as multiple gestation, premature birth, and low birth weight. Furthermore, many studies fail to account for the increased risk of many of these pathologies in the offspring of subfertile women in general. Lastly, the absolute risk of most of the ailments studied is extremely low. In nearly all examples, the number of women who would need to be treated to observe one additional diagnosis is substantially high. When compared with the number of couples who would have remained childless due to severe male factor infertility or would have been exposed to the risk of passing on a severe monogenic disorder, the general increased risks to ART-exposed children is very small.
Keywords: assisted reproductive technologies; embryo culture; IVF offspring; multiple gestations; single embryo transfer